Histopathological spectrum of salivary gland lesions in a tertiary care hospital - Kasundra, Khushbu N.; Patel, Pulkit J. (International Journal of Research in Medical Sciences, 2023)
Background: Salivary gland has a wide spectrum of neoplasms with diverse clinical and morphological features. These tumors are relatively rare. Histopathological examination plays an important role in diagnosis of these tumors. The aim of present study is to evaluate spectrum of salivary gland tumors and their frequency, age, gender and site wise distribution. Methods: The present observational study included 53 cases of salivary gland lesions. Clinical details and histopathological findings were noted from records and obtained data were analyzed using proper statistical software. Results: Out of 53 cases studied, 10 (19%) cases were non-neoplastic, 31 (58%) were benign and 12 (23%) cases were malignant. Benign salivary gland tumors were more common in 4th decade while malignant tumors were common in 5th-6th decade of life. Male to female ratio was 1.52:1. Most of the tumors were located in major salivary gland amongst which parotid gland is the most common one involved. Pleomorphic adenoma was the most common salivary gland tumor amongst all. Mucoepidermoid carcinoma was the most common malignant tumor. Conclusions: Histopathological examination plays an important role in diagnosis and categorization of salivary gland tumors as these tumors are difficult to diagnose based only on morphology and clinical features.